Factors affecting visitors’ memorable wine tourism experiences at the Urla Vineyard Route (Türkiye – Aegean coast) - Türker, Nuray (Turyzm/Tourism, 2025)
This paper aims to identify the key factors that contribute to a memorable wine tourism experience for visitors to the Urla Vineyard Route (UVR). This route the second most important wine tourism route in Türkiye after the Thrace Vineyard Route, was created by seven vineyard owners in 2015. In the research 378 comments of visitors posted on TripAdvisor between 2016 and 2023 were collected and the data was analyzed using MAXQDA Analytics Pro 2020 software. This research employed the netnographic research process. Results show that six factors affect visitors’ wine tourism experiences: the scenery and atmosphere of the vineyard and winery, winery staff, grape variety, food taste, wine tasting and price. Scenery is the most influential factor, while the price is the least in visitors’ wine tourism experiences.